2006
DOI: 10.1063/1.2180786
|View full text |Cite
|
Sign up to set email alerts
|

α and β relaxation dynamics of a fragile plastic crystal

Abstract: We present a thorough dielectric investigation of the relaxation dynamics of plastic crystalline Freon112, which exhibits freezing of the orientational degrees of freedom into a glassy crystal below 90 K. Among other plastic crystals, Freon112 stands out by being relatively fragile within Angell's classification scheme and by showing an unusually strong β-relaxation. Comparing the results to those on Freon112a, having only a single molecular conformation, points to the importance of the presence of two molecul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
58
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 64 publications
7
58
0
Order By: Relevance
“…Most plastic crystals (including cyclo-octanol 22 ) can be characterized as rather "strong" glass formers 17,23 within the strong/fragile classification scheme used to account for the different degrees of deviations from Arrhenius behavior of the -relaxation time. 24 Thus 60SN-40GN is an especially Electronic mail: peter.lunkenheimer@physik.uni-augsburg.de interesting system as it represents one of the rare examples 25 of a relatively fragile plastic crystal. 20,23,26 Thus it is well suited to check if the relation between apparent energy barrier and N corr , suggested for structural glass formers, 6 holds in plastic crystals, too: For a fragile material this relation should lead to a significantly stronger variation of N corr than the relatively weak temperature dependence observed in cyclo-octanol.…”
Section: Introductionmentioning
confidence: 99%
“…Most plastic crystals (including cyclo-octanol 22 ) can be characterized as rather "strong" glass formers 17,23 within the strong/fragile classification scheme used to account for the different degrees of deviations from Arrhenius behavior of the -relaxation time. 24 Thus 60SN-40GN is an especially Electronic mail: peter.lunkenheimer@physik.uni-augsburg.de interesting system as it represents one of the rare examples 25 of a relatively fragile plastic crystal. 20,23,26 Thus it is well suited to check if the relation between apparent energy barrier and N corr , suggested for structural glass formers, 6 holds in plastic crystals, too: For a fragile material this relation should lead to a significantly stronger variation of N corr than the relatively weak temperature dependence observed in cyclo-octanol.…”
Section: Introductionmentioning
confidence: 99%
“…26 Nevertheless, studies of the structure at the inter-and intramolecular scale showed that the interplay of features at these two different length scales may explain the complex dynamics of F-112. [27][28][29] The present work is focused on the determination of the intramolecular structure of F-112, its interplay with intermolecular ordering in the liquid phase, and a deep analysis of the short-range order, and is organized as follows: After a short description of the experimental and simulation procedures, a fit method to obtain molecular parameters from the neutron diffraction data is presented. The intramolecular structure of F-112 will then be obtained from experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19] Halogen-ethane derivatives have been thoroughly characterized macroscopically (heat capacity, thermodynamic magnitudes, phase transitions, etc.) and microscopically (molecular dynamics, crystallographic structure, relaxation dynamics, molecular structure, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…seeking to find a relation between its physical properties and its intermolecular interactions, as well as its intramolecular features, which can influence both the short-and the long-range order. [14][15][16][17][18][19][20][21][22] F-112 and F-113 are archetypal examples in which a mixture of conformers is present, and for which a complicated sequence of calorimetric transitions appears. Figure 1 shows the two F-112 conformers, gauche and trans, and the two F-113 conformers, C 1 and C s .…”
Section: Introductionmentioning
confidence: 99%